Evaluation of the Anxiety Prevalence Relative to Musical Performance in Classical Musicians - Damas, Carlos A. M. de C. e (2017)
Music performance anxiety is a problem that affects musicians. This type of anxiety can generate psychological and physiological symptoms, sometimes can be debilitating, in many situations interfere with the quality of the performance. The present study aims analyze quantitatively, the levels of music performance anxiety of classical music teachers, singers and instrumentalists who are active in mainland Portugal and autonomous regions. A survey was carried out with a questionnaire, in which professional musicians and students (n = 188) participated voluntarily. The results revealed that 86.7% of the musicians reported suffering with the problem. The use of drugs, alcohol and psychotropic substances to deal with the problem was also analyzed.We conclude that the music performance anxiety affects most of the musicians and that it would be pertinent to carry out more investigations that would allow to study and to know the problem better.